Governments and Marriage Education Policy - van Acker, Elizabeth. author. aut Link
XII, 249 p.
Keywords: This book examines the role governments play in managing policy challenges such as religion, romance, gender relations, same-sex marriages and privacy protection in response to social changes in marriage. Elizabeth van Acker asks whether governments can or should intervene in this personal sphere.